Proceedings of the 2011 SIGGRAPH Asia Conference 2011
DOI: 10.1145/2024156.2024182
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of depth maps with multiple scales

Abstract: Multi-view stereo systems can produce depth maps with large variations in viewing parameters, yielding vastly different sampling rates of the observed surface. We present a new method for surface reconstruction by integrating a set of registered depth maps with dramatically varying sampling rate. The method is based on the construction of a hierarchical signed distance field represented in an incomplete primal octree by incrementally adding triangulated depth maps. Due to the adaptive data structure, our algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 32 publications
0
51
0
Order By: Relevance
“…When a scene is covered with scans at different scales, fine resolution surface details can be lost. Fuhrmann and Goesele [21] developed a hierarchical volume approach to retain the maximum amount of details. However, the method is designed to combine a very high number of viewpoints for off-line processing; as such, it is unsuited to real-time use.…”
Section: Visibility Methodsmentioning
confidence: 99%
“…When a scene is covered with scans at different scales, fine resolution surface details can be lost. Fuhrmann and Goesele [21] developed a hierarchical volume approach to retain the maximum amount of details. However, the method is designed to combine a very high number of viewpoints for off-line processing; as such, it is unsuited to real-time use.…”
Section: Visibility Methodsmentioning
confidence: 99%
“…Common representations for 3D models include point clouds, surfels [10], triangle meshes [27], and signed distance functions [6]. Octrees allow for efficient data storage and fusion at multiple scales [9,24,28]. While KinectFusion [17] demonstrated that impressive 3D models can be acquired by tracking and fusing the depth images directly into a signed distance volume, drift will accumulate in the 3D model and inevitably lead to inconsistencies.…”
Section: Related Workmentioning
confidence: 99%
“…However, depth samples across views possessing different scales is challenging for VRIP approaches. One example addressing this issue is the scale space representation presented in (Fuhrmann and Goesele, 2011). They build a multi-level octree holding vertices at different scales.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to (Fuhrmann and Goesele, 2011) we first assign points to an multi-level octree structure according to the pixel footprint. Subsequent filter operations are then carried out on points of the locally lowest tree-levels, whereas high level points are discarded.…”
Section: Introductionmentioning
confidence: 99%